Vertical Bargaining and Retail Competition: What Drives Countervailing Power?. (10th August 2017) - Gaudin, Germain
Abstract: This article investigates the effects of changes in market concentration on the equilibrium prices in a supply chain. Results are derived from a theoretical model of bilateral bargaining between upstream and downstream firms which allows for general forms of demand and retail competition. Whether countervailing buyer power arises, in the form of lower input prices following greater concentration downstream, depends on the pass‐through rate of input prices to retail prices. Countervailing buyer power generally does not translate into lower retail prices because of heightened market power at the retail level.